АДМИНИСТРАТИВНО-ПРАВОВОЙ ПОРЯДОК ПРЕКРАЩЕНИЯ ДЕЯТЕЛЬНОСТИ ФИЗИЧЕСКОГО ЛИЦА ПРЕДПРИНИМАТЕЛЯ В УКРАИНЕ - Бандурка, Сергей Сергеевич (SUPREMANCE OF LAW, 2018)
Entrepreneurial activity is an integral part of ensuring national security, since the mechanism of entrepreneurship is the basis for the economic development of the state. Successful development of entrepreneurial activity is possible only if all the norms of legislation regulating the entire business process from its registration to termination are observed. Entrepreneurial activity is regulated by the norms of various branches of law, in particular economic, civil, labor, administrative. Protection of the security of business activity is carried out in the civil law, criminal law and administrative law. In the context of the economic development of the legal regulation of economic activity, the clarity and validity of the legal cessation of entrepreneurial activity, in particular the administrative and legal order of termination of the activity of an individual entrepreneur, is of particular importance. The total number of private entrepreneurs in Ukraine in 2017 after the innovations in the tax legislation decreased by more than 120 thousand. The termination of their activities was accompanied by conflicts in relations with the tax administration and executive bodies. In this regard, there is a need for additional analysis of the administrative and legal order of termination of the activities of a physical person - an entrepreneur in Ukraine. The administrative and legal basis for the termination of the activity of a physical person engaged in entrepreneurial activity is investigated. The procedure for termination of entrepreneurial activity was studied.
Keywords: individual - entrepreneur; order termination of entrepreneurial activity; state registration; single social contribution; taxation